Subject-variability effects on micron particle deposition in human nasal cavities. (January 2018) - Calmet, H.; Kleinstreuer, C.; Houzeaux, G.; Kolanjiyil, A.V.; Lehmkuhl, O.; Olivares, E.; Vázquez, M.
Abstract: Validated computer simulations of the airflow and particle dynamics in human nasal cavities are important for local, segmental and total deposition predictions of both inhaled toxic and therapeutic particles. Considering three, quite different subject-specific nasal airway configurations, micron-particle transport and deposition for low-to-medium flow rates have been analyzed. Of special interest was the olfactory region from which deposited drugs could readily migrate to the central nervous system for effective treatment. A secondary objective was the development of a new dimensionless group with which total particle deposition efficiency curves are very similar for all airway models, i.e., greatly reducing the impact of intersubject variability. Assuming dilute particle suspensions with inhalation flow rates ranging from 7.5 to 20 L/min, the airflow and particle-trajectory equations were solved in parallel with the in-house, multi-purpose Alya program at the Barcelona Supercomputing Center. The geometrically complex nasal airways generated intriguing airflow fields where the three subject models exhibit among them both similar as well as diverse flow structures and wall shear stress distributions, all related to the coupled particle transport and deposition. Nevertheless, with the new Stokes-Reynolds-number group, Stk 1.23 Re 1.28, the total deposition-efficiency curves for all three subjects and flow rates almost collapsed to a single function. However, local particle deposition efficiencies differed significantly for the three subjects when using particle diameters d p = 2, 10, and 20 μ m . Only one of the three subject-specific olfactory regions received, at relatively high values of the inertial parameter d p 2 Q, some inhaled microspheres. Clearly, for drug delivery to the brain via the olfactory region, a new method of directional inhalation of nanoparticles would have to be implemented.